2023
DOI: 10.1101/2023.04.19.537538
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple domains of the integral KREPA3 protein are critical for the structure and precise functions of RNA Editing Catalytic Complexes inTrypanosoma brucei

Abstract: The gRNA directed U-insertion and deletion editing of mitochondrial mRNAs that is essential in different life cycle stages for the protozoan parasite Trypanosoma brucei is performed by three similar multi-protein catalytic complexes (CCs) that contain the requisite enzymes. These CCs also contain a common set of eight proteins that have no apparent direct catalytic function, including six that have an OB-fold domain. We show here that one of these OB-fold proteins, KREPA3 (A3), has structural homology to other… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Several RECC protein mutagenesis studies, including of B5-B8 that contain RNase III-like domains, have identified single amino acid substitutions with different consequences on BF vs. PF cell growth and RECC integrities (Carnes et al, 2011;McDermott et al, 2015a, b;McDermott and Stuart, 2017;McDermott et al, 2019;Carnes et al, 2022;Davidge et al, 2023). Therefore, we hypothesized that we might also observe life cycle stage differences in the growth of cells containing substitutions that were identified in our BF B4 deep mutational scan.…”
Section: Life-cycle Stage Differences In Fitness Of Cells Containing ...mentioning
confidence: 80%
See 4 more Smart Citations
“…Several RECC protein mutagenesis studies, including of B5-B8 that contain RNase III-like domains, have identified single amino acid substitutions with different consequences on BF vs. PF cell growth and RECC integrities (Carnes et al, 2011;McDermott et al, 2015a, b;McDermott and Stuart, 2017;McDermott et al, 2019;Carnes et al, 2022;Davidge et al, 2023). Therefore, we hypothesized that we might also observe life cycle stage differences in the growth of cells containing substitutions that were identified in our BF B4 deep mutational scan.…”
Section: Life-cycle Stage Differences In Fitness Of Cells Containing ...mentioning
confidence: 80%
“…Functional annotation of evolutionarily divergent trypanosomatid proteins with limited sequence homology to other eukaryotic proteins can be advanced by mutagenesis combined with novel high-throughput functional analyses (McDermott et al, 2015a;Carnes et al, 2022;Davidge et al, 2023). Here we describe the development of a deep mutational scanning approach for T. brucei, which makes use of tet-conditional expression of a wild-type gene of interest and constitutive expression of a library of mutant variants (McDermott et al, 2015a;McDermott and Stuart, 2017), a high-throughput sequencing readout for cell growth upon exclusive expression of mutant variants (Wei and Li, 2023), and freely available computational tools to estimate variant fitness (Faure et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations